Work function lowering of LaB6 by monolayer hexagonal boron nitride coating for improved photo- and thermionic-cathodes - Yamaguchi, Hisato; Yusa, Ryunosuke; Wang, Gaoxue; Pettes, Michael T.; Liu, Fangze; Tsuda, Yasutaka; Yoshigoe, Akitaka; Abukawa, Tadashi; Moody, Nathan A.; Ogawa, Shuichi (Applied physics letters, 2023)
We report a lowering of work function for lanthanum hexaboride (LaB6) by monolayer hexagonal boron nitride (hBN) coating. Photoemission electron microcopy (PEEM) and thermionic emission electron microscopy (TEEM) both revealed that the hBN coated region of a LaB6 (100) single crystal has a lower work function compared to the bare (i.e., non-coated) and graphene coated regions. A broad and uniform brighter image of the hBN coated region in PEEM was quantitatively supported by a 0.4 eV decrease in the work function in photoelectron spectra compared to the bare region. TEEM results were consistent in that the hBN coated region exhibited thermionic emission at 905 °C, whereas the bare and graphene coated regions did not. A larger decrease in the work function for hBN coated LaB6 (100) compared to graphene coated LaB6 (100) was qualitatively supported by our density functional theory calculations. Adding an oxide layer in the calculations improved consistency between the calculation and experimental results. We followed up our calculations with synchrotron-radiation x-ray photoelectron spectroscopy and confirmed the presence of an oxide layer on our LaB6.